Beyond criminal justice: connecting justice and sustainability. Issue 3 (1st September 2016) - Hallenberg, K.M.; Haddow, C.
Abstract : The potential of higher education in advancing sustainability has been widely accepted and even partly realised, although a wholesale reorientation of core activities and curricula toward and embedded with sustainability is still an exception. But even big changes start small and modules that address sustainability have both strategic and symbolic value particularly in disciplines and departments where it has not previously been explicitly, or at all, addressed. This paper discusses a project which aims to introduce sustainability considerations into the criminology and criminal justice curriculum by way of a new and innovative module "Criminology for a Just Society", developed with the support and funding from the central university sustainability initiative. The module aims to facilitate a broad and nuanced understanding of sustainability and criminology's potential to further it, focusing on the current ecological, cultural, socio-political and economic problems and ways of addressing them. This is done through a framework of (in)justice which allows students to embed new understanding within familiar disciplinary context and language. The pedagogical approach is interdisciplinary, emphasising service learning through volunteering placements and active student engagement, and assessment which embeds critical reflection and knowledge exchange. "Criminology for a Just Society" was piloted in 2014–2015 and the paper reflects on the project, drawing from both student and staff experiences to evaluate its impact and map further developments.